2020
DOI: 10.21037/tcr-19-2017
|View full text |Cite
|
Sign up to set email alerts
|

Different primers for diagnosing circulating cell-free DNA of colorectal cancer

Abstract: Background Cell-free DNA (cfDNA) primers have been designed to screen for cancer diagnosis, but the results have been inconsistent. The study aimed to compare different primers for diagnosing cfDNA of colorectal cancer (CRC). Methods Peripheral blood specimens were collected from 71 patients with CRC and 20 patients with proliferative intestinal polyps. Quantitative polymerase chain reaction (q-PCR) was used to detect the concentration of cfDNA of these primers, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The level of cfDNA in different studies varies, which may be explained by the fact that there are no unified standards for specimen type, specimen collection process, detection method, and accuracy of test equipment. Generally, when quantitatively detecting cfDNA, each laboratory will choose different reference genes, such as β-actin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and long interspersed element-1 (LINE-1) ( 10 , 11 ), etc., whose common feature is that they can exist and express stably. However, due to their different copy numbers, it is possible for the test results to vary.…”
Section: Discussionmentioning
confidence: 99%
“…The level of cfDNA in different studies varies, which may be explained by the fact that there are no unified standards for specimen type, specimen collection process, detection method, and accuracy of test equipment. Generally, when quantitatively detecting cfDNA, each laboratory will choose different reference genes, such as β-actin, glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and long interspersed element-1 (LINE-1) ( 10 , 11 ), etc., whose common feature is that they can exist and express stably. However, due to their different copy numbers, it is possible for the test results to vary.…”
Section: Discussionmentioning
confidence: 99%
“…By detecting housekeeping genes ( Aucamp et al, 2016 ) or noncoding repetitive sequences ( Hussein et al, 2019 ) in cfDNA and fitting the standard curve with a reference substance ( Tang et al, 2020 ), absolute cfDNA concentrations can be quantified using PCR-based methods. Frequently used reference genes include TERT ( Akuta et al, 2020 ), GAPDH ( Salinas-Sanchez et al, 2021 ), EGFR ( Sugimoto et al, 2023 ), KRAS ( Berchuck et al, 2022 ), and ALU ( Shi et al, 2020 ). However, the lack of unified reference genes results in significant variations in the quantitative results of PCR-based methods, hindering efficient comparisons across different studies ( Devonshire et al, 2014 ).…”
Section: Preanalytical Variables Affecting Cfdna Analysismentioning
confidence: 99%
“…A recent case-control study identified 3 novel lncRNAs, XLOC_006844, LOC152578, and XLOC_000303, using highthroughput lncRNA microarray. These were found to be upregulated in CRC patients when compared to HCs, with AUCs of 0.919 and 0.975 in the training and validation sets respectively, hinting at their potential as a biomarker panel for CRC detection [ 160 ]. Gharib et al [ 161 ] examined the levels of a panel of 10 significantly dysregulated lncRNAs (CCAT1, CCAT2, H19, HOTAIR, HULC, MALAT1, PCAT1, MEG3, PTENP1, and TUSC7) identified in stool samples from 150 CRC patients.…”
Section: Long Noncoding Rnasmentioning
confidence: 99%